Case report: Satralizumab as an adjunctive therapy for AQP-4 antibody and MOG antibody dual-negative optic neuritis in a third-trimester pregnancy case - Sun, Chuanbin; Liu, Zhe (Frontiers in Medicine, 2024)
Therapy of demyelinating optic neuritis (DON) in pregnant cases is challenging, especially when the pregnant DON case showed poor response to intravenous methylprednisolone pulse therapy (IVMP), and even to an intravenous immunoglobulin therapy (IVIG). We herein report a case of a 28-year-old pregnant woman with sequential severe visual loss in both eyes. She presented to the local hospital with a main complaint of sudden, painless visual loss in the left eye, and was diagnosed as DON in the left eye, but got no orbital MRI examination or IVMP therapy for safety concerns. At admission in our hospital, her visual acuity was 20/30 and no light perception in the right and left eye respectively, and her right eye vision continuously deteriorated to 20/1000 one day after admission. Ophthalmic examination revealed normal anterior segment and swollen optic disc in the right eye, and dilated pupil with relative afferent pupillary defect, swollen optic disc in the left eye. Serological tests for common pathogens, AQP-4 Ab, MOG-Ab, and other common autoantibodies were all negative. The patient was clinically diagnosed as DON in both eyes, and was performed seven days of IVMP and four days of IVIG therapy, but got no visual improvement. Three-dosed satralizumab 120 mg was then subcutaneously injected in the acute stage of DON in this case, combined with slowly tapered oral methylprednisolone. Two months after the first injection of satralizumab, the patient naturally delivered a healthy female infant weighing 2305 g at 36 weeks and 1 day of gestation, and her visual acuity was improved to 20/500 in both eyes, then slightly increased to 20/320 in both eyes another two months later, and kept stable during subsequent follow-up. The infant was fed with formula milk powder and grew up normally. No systemic or ocular side effects related to satralizumab therapy were found in the patient and fetus/infant during 9 months follow-up. Our findings in this case indicate that satralizumab may be a safe and efficient adjunctive therapy in pregnant DON case poorly responding to IVMP and IVIG theray, even though the DON is an AQP-4 Ab and MOG-Ab dual negative one.